Synthetic Methodologies for Si‐Containing Li‐Storage Electrode Materials. Issue 4 (9th February 2022) - Zhou, Jie; Lin, Ning
Abstract : Silicon is regarded as the most promising anode candidate for improving the energy density of next‐generation Li‐ion batteries (LIBs) because of the high specific capacity of 4200 mAh g −1, low working voltage, and natural abundance. It is well demonstrated that the serious issues such as huge volume expansion and intrinsic low conductivity of Si anode can be addressed by nanoengineering and compositing strategies. An important step toward fully realizing the practical application of the Si‐containing electrode lies in producing high‐quality materials on large scale. Therefore, a controllable, high‐efficient, low‐cost, and environment‐friendly synthetic methodology is required to fabricate Si‐containing anode materials with high tap density, low specific surface area, high conductivity, chemical and structural stability, and high purity, thus leading to high Coulombic efficiency, high specific capacity, long cycling stability, and superior rate capability. In this review, the effects and bottlenecks of synthetic methodologies for the developments of Si anode are emphasized. The well‐developed physical and chemical synthetic approaches of nano‐ and microstructured Si, Si‐based composites, and Si–graphite hybrid electrode materials are summarized. In each category, the main merits and limitations of different synthetic methods are discussed from both academic and industrial points of view. Finally, this review ends with a conclusion of these synthetic routes, and a brief perspective on the future direction of Si‐containing Li‐storage materials for practical LIBs. Abstract : Herein, the well‐developed physical and chemical synthetic approaches for Si, Si‐based composites, and Si–graphite hybrid electrode materials are summarized. In each category, the main merits and limitations of different methods are discussed from both academic and industrial points of view. Finally, a brief perspective on the future direction of Si‐containing Li‐storage materials for practical LIBs is discussed.